Knowledge of Human Papillomavirus, Risk Factors and Screening for Cervical Cancer Among Women in Ghana - Yvonne Nartey PhD; Kwabena Amo-Antwi MD; Betty Osei-Ntiamoah Mphil; Philip C Hill PhD; Edward T. Dassah PhD; Richard H. Asmah PhD; Kofi M. Nyarko PhD; Ramatu Agambire PhD; Thomas O. Konney MD; Joel Yarney MD; Nelson Damale MD; Brian Cox PhD (Cancer Control)
Background Cervical cancer ranks as the fourth most common cancer among women, with 662,301 new cases and 348,874 deaths reported in 2022. The majority of the disease burden occurs in low- and middle-income countries. In Ghana, there were 3072 new cases and 1815 deaths reported in 2022. While human papillomavirus (HPV) infection, a key cause for cervical cancer, resolves in most individuals, it can progress to cancer in some. This has led to research into other factors that may, in conjunction with HPV, increase the risk of cervical cancer progression. Improving knowledge of HPV, risk factors, and screening will be important in reducing the burden of cervical cancer. In this study, we investigate the knowledge on HPV, risk factors, and cervical screening among women in Ghana. Methods A hospital-based case-control study was conducted among women aged 18 to 95 years. This involved Ghanaian women diagnosed with cervical cancer and hospital controls. Data were collected using a structured questionnaire, and basic descriptive analyses were performed. Results Results from the 206 cases and 230 controls revealed limited knowledge about HPV and its role in cervical cancer development, with minimal disparity between women with (2.4%) and without (6.5%) cervical cancer. The majority of participants lacked awareness of HPV transmission (95.9%), and awareness of HPV vaccination was low (3.5%). Barriers to HPV vaccination included insufficient awareness about HPV, limited access to vaccination centers, and cost concerns. Respondents expressed a preference for educational programs delivered through church, radio, and television channels. Conclusions Knowledge of HPV, risk factors, and cervical screening was found to be very low among Ghanaian women. These findings underscore the need for a comprehensive cervical cancer educational initiative within Ghana’s national cervical cancer control policy to mitigate the disease’s impact.